Alternative DNA Repair During Meiosis in the Budding Yeast S. cerevisiae - Reeves, Ryan Peter (2025)
In order for meiosis to occur, DNA double-strand breaks (DSBs) must be induced and subsequently repaired in a homology directed manner; this process is called meiotic recombination. As unrepaired DSBs can have catastrophic consequences for cells, meiotic recombination must be tightly regulated. Despite being studied for decades, new evidence suggests that novel repair pathways and mechanisms are at play during meiosis. By using the budding yeast S. cerevisiae, two alternative DSB repair mechanisms were investigated to readdress our understanding of meiotic DSB processing. The first involves an uncharacterised way of removing the DSB-inducing enzyme Spo11 from DNA. The second seeks to understand which DSB repair pathway is leading to gross chromosomal rearrangements during meiosis. Meiotic DSBs are initiated by Spo11, which cuts DNA but remains covalently attached. The Spo11 ‘roadblock’ must be removed from the DNA for meiosis to progress. This action is undertaken nucleolytically by the MRX complex, which cleaves the DNA which the Spo11 is bound to (Neale et al., 2005). Whilst this method of Spo11 release via MRX-induced cleavage has long been demonstrated, an alternative mechanism has been overlooked. A recent study showed that when the MRX complex is compromised, recombinant DNA products can be produced (Yun and Kim, 2019), indicating that the Spo11 has somehow been removed independently of the MRX complex. We hypothesised that Spo11 is being removed from DNA by the phosphodiesterase Tdp1, which is upregulated in meiotic prophase (Kugou et al., 2007) and has been shown to remove similar protein adducts from DNA (Nitiss et al., 2006). By investigating this mechanism through fluorescent reporter strains, western blotting, PFGEs and Southern blotting, it was determined that Tdp1 isn’t responsible for the alternative Spo11 removal mechanism. The second part of this project seeks to define a homology-directed annealing pathway which is utilised to repair meiotic DSBs. This pathway is repairing DNA at non-allelic loci, a process referred to as ectopic recombination, which can generate gross chromosomal rearrangements (Grushcow et al., 1999). Ectopic recombination occurs around 1 % of the time during meiosis in wildtype S. cerevisiae and is upregulated in strains lacking the checkpoint protein Rad24 (Grushcow et al., 1999, Shinohara and Shinohara, 2013). It was recently shown that whilst short regions of homology are utilised, this pathway is independent of the RecA recombinase homologs Rad51 and Dmc1 (Allison et al., 2023), indicating a pathway which doesn’t utilise strand-invasion. The single strand annealing pathway (SSA) utilises Rad52-Rad59 to anneal ssDNA together with 60-200 bp of homology, with the nuclease complex Rad1-Rad10 required to trim non-homologous trails (Sugawara et al., 2000, Fishman-Lobell et al., 1992). This study shows that the SSA proteins Rad1, Rad10, Rad52, and Rad59 are all present during meiosis in wildtype and rad24Δ backgrounds, and that Rad59 is more abundant in a rad24Δ background when compared to wildtype